Obsessive-compulsive disorder triggered by news of contaminated food - Masiran, Ruziana; Abdul Latib, Farah Adiba Maliha (BMJ Publishing Group, 2024)
We present a case of a woman in her early 30s who developed severe obsessive-compulsive disorder symptoms following exposure to news reports about instant noodles allegedly contaminated with a carcinogenic substance. The news triggered an overwhelming fear of ingesting harmful food associated with persistent and intrusive thoughts about contamination in this patient. As a result, she adopted extreme food avoidance behaviours and restricted her oral intake for two weeks, causing significant weight loss and anxiety. Following a visit to her psychiatrist and a prescription for a selective serotonin reuptake inhibitor, her eating behaviours improved, and she could take her food without overwhelming fear. This case shows how OCD may mimic eating disorders and highlights how food-related obsessions can severely impact health.